2018
DOI: 10.1097/mnh.0000000000000415
|View full text |Cite
|
Sign up to set email alerts
|

α-Klothoʼs effects on mineral homeostasis are fibroblast growth factor-23 dependent

Abstract: Purpose of reviewα-Klotho (Klotho) occurs in three isoforms, a membrane-bound form acting as a coreceptor for fibroblast growth factor-23 (FGF23) signalling, a shed soluble form consisting of Klotho's large ectodomain thought to act as an enzyme or a hormone, and a secreted truncated form generated by alternative splicing of the Klotho mRNA with unknown function. The purpose of this review is to highlight the recent advances in our understanding of Klotho's function in mineral homeostasis.Recent findingsA numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…( 101,102 ) However, Anour and colleagues ( 103 ) demonstrated that Klotho lacks a vitamin D‐independent physiological role in glucose homeostasis, bone turnover, and steady‐state PTH secretion, in vivo, casting doubt on Klotho alone as a bona fide regulator of any of these phenomena. In a sense, this original research by the Erben group ( 103 ) was prescient and consistent with the recent opinion piece ( 50 ) that “Klotho's effects on mineral homeostasis are fibroblast growth factor‐23 dependent.” Are all Klotho actions dependent upon FGFR1 signal transduction initiated by FGF23? This is the provocative question regarding Klotho in 2020!…”
Section: Renal Klotho Regulation By 125(oh)2d Occurs Via a Primary Gsupporting
confidence: 76%
See 3 more Smart Citations
“…( 101,102 ) However, Anour and colleagues ( 103 ) demonstrated that Klotho lacks a vitamin D‐independent physiological role in glucose homeostasis, bone turnover, and steady‐state PTH secretion, in vivo, casting doubt on Klotho alone as a bona fide regulator of any of these phenomena. In a sense, this original research by the Erben group ( 103 ) was prescient and consistent with the recent opinion piece ( 50 ) that “Klotho's effects on mineral homeostasis are fibroblast growth factor‐23 dependent.” Are all Klotho actions dependent upon FGFR1 signal transduction initiated by FGF23? This is the provocative question regarding Klotho in 2020!…”
Section: Renal Klotho Regulation By 125(oh)2d Occurs Via a Primary Gsupporting
confidence: 76%
“…3) via ERK1/2, SGK1, and WNK4 to depress endocytotic removal of TRPV5 from the plasma membrane. ( 50 ) Thus, 1,25(OH) 2 D, by independently inducing TRPV5 ( 82 ) and Klotho, ( 70 ) apparently elicits FGF23‐driven calcium retention at the kidneys. One could speculate, therefore, that 1,25(OH) 2 D/VDR–RXR chronically initiates calcium conservation at the kidneys over a lifetime, possibly to lower the incidence of osteoporosis.…”
Section: Renal Klotho Regulation By 125(oh)2d Occurs Via a Primary Gmentioning
confidence: 98%
See 2 more Smart Citations
“…Different pathologic entities that affect renal tubules could be linked to Vitamin D dysregulation. Reaching homeostasis in Vitamin D balance could be a pivotal strategy in the treatment of these diseases [6].…”
Section: Introductionmentioning
confidence: 99%